La cultura organizacional y su impacto en el compromiso laboral en tiempos de pandemia de los colaboradores de la división empresas en Rímac Seguros - Arbe Braga, Cecilia Ximena (2021)
When addressing the concept of organizational culture, it is understood that it refers to the relationship between individual values and those of the organization, where both have certain expectations regarding the other; In turn, work commitment refers to the attitudinal results following the relationship between the individual and the organization. There is a certain degree of identification between both concepts, which is why this research had the general objective of determining the impact of the organizational culture on the work commitment in times of pandemic of the employees of the business division in the Insurance Company. . For which a basic type of research was developed, with an explanatory level of study, with a quantitative approach and a non-experimental design. In turn, the sample was made up of a total of 50 employees from the Insurance company, to whom two data collection instruments were applied, a survey and questionnaire adapted from the OCAI for the organizational culture variable and a questionnaire on a Likert-type scale for the work commitment variable. Among the main results, 0.673 was obtained as a correlation coefficient and 0.000 as bilateral significance, indicating a positive and significant relationship between the variables. It was concluded that the organizational culture has an impact on work commitment during the pandemic among the workers of the Insurance company.